ATTITUDES OF EDUCATED YOUTH OF THE SOCIAL STUDIES UNIT TOWARD ENTREPRENEURSHIP (International Journal of Food and Nutritional Sciences, 2022)
This current study aims to explore the attitudes of educated youths of social studies towardsentrepreneurship as well as their implications for future career paths and social impact.